Galerie Haas Zürich - Art Cologne. - Galerie Haas AG, Zürich (Köln; Zürich : Art Cologne; Galerie Haas AG, 2008)
Baselitz, Georg ; Baskin, Leonard ; Christian, Abraham David ; Denker, Martin ; Erben, Ulrich ; Feuser, Christina ; Gartner, Marianna ; Graubner, Gotthard ; Kanovitz, Howard ; Klapheck, Konrad ; Klein, Astrid ; Kluge, Gustav ; Kuehn, Gary ; Wirths, René ; Lucander, Robert ; Meese, Jonathan ; Nelson, Kenton ; Ottersbach, Heribert C. ; Platen, Angelika ; Polke, Sigmar ; Rattray, Diane ; Stella, Frank
Duits
Exhibition. Art Cologne 2008. Art Cologne Köln. 2008-04-16. 2008-04-20
boek